Development of efficient and stable inverted bulk heterojunction (BHJ) solar cells using different metal oxide interfaces - Litzov, Ivan; Brabec, Christoph (Materials, 2013)
Solution-processed inverted bulk heterojunction (BHJ) solar cells have gained much more attention during the last decade, because of their significantly better environmental stability compared to the normal architecture BHJ solar cells. Transparent metal oxides (MeO) play an important role as the dominant class for solution-processed interface materials in this development, due to their excellent optical transparency, their relatively high electrical conductivity and their tunable work function. This article reviews the advantages and disadvantages of the most common synthesis methods used for the wet chemical preparation of the most relevant n-type- and p-type-like MeO interface materials consisting of binary compounds AB. Their performance for applications as electron transport/extraction layers (ETL/EEL) and as hole transport/extraction layers (HTL/HEL) in inverted BHJ solar cells will be reviewed and discussed. © copy 2013 by the authors; licensee MDPI, Basel, Switzerland.
Keywords: Device stability; Inverted structure; Metal oxide interfaces; Sol-gel methods